Early Oligocene terrestrial vertebrates from Belgium (Borgloon Formation, MP 21): catalog and interpretation of recent data - Smith, Richard (Coloquios de Paleontología, 2003)
The history of fossil vertebrate discoveries and papers concerning the sites of Hoogbutsel and Hoeleden (Brabant, Belgium) are given. The faunal list of the vertebrates (MP 21) is composed on the basis of the data published during the last fifty years. The biostratigraphical interpretation of the Hoogbutsel locality as well as the paleoecological data resulting from the taphonomical investigation are discussed. The first data concerning the discovery of the probably coeval new mammal site Boutersem TGV are given.
Keywords: Vertebrates; Early Oligocene; Hoogbutsel; Hoeleden; Boutersem TGV; Belgium